SMART e-Cons: an effort to Expand Educational Access for Gersik Village Communities - Yudi Kurniawan; Riski Muliyani; Eti Sunarsih; Dewi Mariana (International Journal of Public Devotion, 2019)
The lack of residents’ awareness to advance their study to University in the border area of Jagoi Babang District, West Kalimantan, Indonesia made the pupils around the border area almost less educate or stagnant both in the numbers and quality of their education. There are many residents of the high school age was drop out or did not advance their school to university level. But ironically, almost all resident has android cellphone but it functional as calling and messaging only.This program offers an alternate solution for local resident to get access of higher education information by using their cellphones. This program called ad SMART e-Cons. This was private service that provide by our team for facilitate the local residents’ curiosity about process in higher education. Most of the local pupils has working as farmer, as cotter so it has been most difficulties for us to gather all of them in one time. Therefore, from 138 families only there are 34 family’s members had been volunteer for this program. And this was reasoning why our team has decided to deliver the SMART e-Cons sheets to their house (all of residents) include volunteer that present in main session.This program was implemented by using the method of coordination, implementation to reporting. These activities can also contribute to increase information about the importance of education in university which certainly has many entry channels including through scholarships.This program’s result that 53% resident able to access the link and able to give feedback for the team, 50% able to access the link only, and 100% resident able to give feedback only (doesn’t know to click the link).Finally, our purpose to give a brief explanation for local residents of Gersik Village about entrances university both in country and overseas university without worries about tuitions fee and sort of kinds.